Assessment of Conventional Counseling Technique: Basis For Scripture-Based Counseling - Genesis Balongkit Naparan (Faculty of Teacher Training and Education, Universitas Terbuka, 2020)
This research evaluated the process of conventional counseling techniques in one of the private higher educational institutions to improve its counseling services. This research also aimed at inviting more college students to submit themselves to the counseling process. This study employed a qualitative case study design of Yin (2014) using 32 research participants as key informants: 30 counselees and two guidance counselors. The evaluation of conventional counseling is based on Pal's (2011) seven stages in the counseling process: readiness, reception, reconnaissance, examination, interpretation, application, and review. Based on the findings, most of the students who entered the guidance office were not ready for the counseling process. However, the clienteles had a good impression of the counselors that leads to empowerment. Therefore, one way to enhance the practice of conventional counseling in schools is through the utilization of scripture-based counseling.